BISNIS PRODUK SALAD BUAH “LOESTY KITCHEN” SEBAGAI SNACK ALTERNATIF SEJAK MASA PANDEMI COVID-19 - Desak Made Sukarnasih; Dewa Ayu Kadek Pramita; Desak Ayu Sriary Bhegawati (SEMAR : Jurnal Sosial dan Pengabdian Masyarakat, 2023)
In order to retain excellent health, people should make eating nutritious meals a habit.A healthy alternative to eating is fruit salad. Even more, it can both prevent and treat a variety of illnesses. The firm runs the danger of having low-quality or broken ingredients since they are not durable, which would have an influence on the items' quality and lead to fewer people buying fruit salad. The continuing Covid-19 outbreak has marginally slowed the food industry's expansion. Due to limitations on community activities during the pandemic, many SMEs have gone out of business or closed, which has an impact on income, namely a decline in company turnover.This product's marketing strategy includes both direct marketing and the use of social media to spread awareness among consumers and the general public. In order to identify and assess the degree of strengths, weaknesses, opportunities, and threats that business actors may encounter in operating their businesses, SWOT analysis is crucial in the development and management of company operations. On the other side, business owners might benefit from these chances by using digital marketing or online sales. Utilizing internet sales can considerably assist MSME players in overcoming a variety of difficulties during the Covid epidemic.